Prevalence rates for black lung epidemic likely underestimated for coal miners in Appalachia - Royal, Kenneth (Social Determinants of Health, 2019)
Epidemiologists have recently declared coal workers’ pneumoconiosis, more commonly known as “black lung disease”, an epidemic in the economically underserved areas of eastern Kentucky, southwestern Virginia and southern West Virginia. The epidemic was declared after black lung cases increased significantly after decades of declining estimates. The circumstances associated with verifying the presence of black lung disease and obtaining subsequent compensation benefits have a long-standing and controversial history clouded by allegations of bias and corruption. In the article, I question the accuracy of government reported estimates and discuss why true estimates of black lung disease likely are greatly underestimated due to a combination of poor data collection methodologies and unique social, cultural, economic and political factors surrounding underserved and vulnerable coal miners in Appalachia.